Backshoring in Light of the Concepts of Divestment and De-internationalization: Similarities and Differences - Michał Młody (Entrepreneurial Business and Economics Review, 2016)
Objective: The purpose of this article is to evaluate the adequacy of the present theoretical knowledge relating to divestments and de-internationalization in the context of explaining the backshoring phenomenon – a relatively new, but gaining in importance specific behaviour of companies in the process of internationalization.